CARDIOVASCULAR DISEASE RISK ASSESSMENT (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
Cardiovascular diseases (CVDs) continue to be a leading cause of morbidity and mortality worldwide. Given the complex interplay of genetic, environmental, and lifestyle factors contributing to CVD, accurate risk assessment is crucial for early intervention and preventive strategies. This scientific article reviews the current methodologies employed in cardiovascular disease risk assessment, discusses their strengths and limitations, and explores emerging trends and future prospects in this critical field. Key topics include traditional risk factors, novel biomarkers, genetic predisposition, and the role of advanced technologies in refining risk prediction models